Design and Application of Inorganic Nanoparticle Superstructures: Current Status and Future challenges - Gao, Yan; Tang, Zhiyong (Small (Weinheim an der Bergstrasse, Germany), 2011)
Self‐assembly of inorganic nanoparticles (NPs) into superstructures, which is used as a general way to integrate functional inorganic NPs into macroscale devices, has attracted much research interest. This review will summarize the recent progress and discuss future challenges of the inorganic NP superstructures. Examples include both DNA‐based and polymer‐based NP assemblies with controlled positioning and geometries, and quasicrystalline ordered structures from the self‐assembly of binary or ternary NPs. Different from their individual NP counterparts, these self‐assembled superstructures possess unique properties, such as optical chirality and dynamic structural change under an external stimulus. Due to their diversified structures and functionalities, inorganic NP superstructures have shown a wide range of promise for applications in electronic and photonic devices, such as field‐effect transistors, magnetoresistive components, optical information recording, and solar cells. Self‐assembly of inorganic nanoparticles into functional superstructures have attracted a lot of attention recently. The combination of inorganic nanoparticles and polymers or DNA gives rise to various applications, for example, photonic storage material. This review summarizes the latest progress in terms of design and application of inorganic nanoparticle superstructures and proposes its future challenges.